Stellar disc streams as probes of the Galactic potential and satellite impacts. Issue 2 (30th August 2018) - Laporte, Chervin F P; Johnston, Kathryn V; Tzanidakis, Anastasios
ABSTRACT: Stars aligned in thin stream-like features (feathers), with widths of δ ∼ 1−10° and lengths as large as Δ l  ∼ 180°, have been observed towards the Anticentre of our Galaxy and their properties mapped in abundances and phase-space. We study their origin by analysing similar features arising in an N -body simulation of a Galactic disc interacting with a Sagittarius-like dwarf spheroidal galaxy (Sgr). By following the orbits of the particles identified as contributing to feathers backwards in time, we trace their excitation to one of Sgr's previous pericentric passages. These particles initially span a large range of phase-angles but a tight range of radii, suggesting they provide a probe of populations in distinct annuli in the outer Galactic disc. The structures are long lived and persist after multiple passages on time-scales of ${\sim }4 \, \rm {Gyrs}$ . On the sky, they exhibit oscillatory motion that can be traced with a single orbit mapped over much of their full length and with amplitudes and gradients similar to those observed. We demonstrate how these properties of feathers may be exploited to measure the potential, its flattening or the existence of a dark matter disc as well as infer the strength of recent potential perturbations.